The effects of the renewed mathematics curriculum on the algebraic thinking levels of the students - Küşat YENİLMEZ; Melike TEKE (İnönü Üniversitesi Eğitim Fakültesi Dergisi)
The aim of this study is to determine the effects of the renewed mathematics curriculum on the algebraic thinking levels of students. The sample of the study contains 24 students who are selected randomly from all the 6th grade students in Alpu district in Eskişehir during 2006-2007. “Development of Algebraic Thinking” test prepared so as to measure the four levels of algebraic thinking defined by Altun (2005) and including the sample questions published by Altun (2005) was administered. In the study single group test-retest model was used. In order to determine the characteristics of the students, a demographical information form was used with the test. After administering the test, the topic “Everyone Must Learn Algebra” in the “Mathematics and Art” unit in the 6th grade was worked up according to the directions as suggested in the teacher’s book for five weeks. One week after the topic was studied, the retest was administered. The collected data was analyzed using paired-samples t-test and independent-samples t-test. The results of the study indicated that there are significant differences between the test and retest data according to the first, second and third levels of algebraic thinking. In addition, after analyzing the total development of the students according to their genders, success, and interest in mathematics, a significant difference was found between in terms of success variable.